Microstructural evaluation of a slurry based Ni/YSZ thermal barrier coating for automotive turbocharger turbine application. (5th November 2016) - Abbas, Muhammad Rabiu; B., Uday M.; Noor, Alias Mohd; Ahmad, Norhayati; Rajoo, Srithar
Abstract: In the present study, the method of slurry coating process was used to fabricate functionally graded thermal barrier coating (FG-TBC) for turbocharger application. An automatic film applicator was used for the coating in an attempt to minimize the production cost of ceramic thermal barrier coatings. Yttria stabilized zirconia ceramic and nickel metal powders were mixed in appropriate proportion and produced a functionally graded material mixture. A slurry based coating method was used for the fabrication of the FG-TBC. The coating compositions of 30 wt% Yttria Stabilized Zirconia and 70 wt% Nickel, 55 wt% Yttria Stabilized Zirconia and 45 wt% Nickel as well as 75 wt% Yttria Stabilized Zirconia and 25 wt% Nickel were used in depositing the first, second and third layers of the functionally graded thermal barrier coating on the substrate respectively. Field Emission Scanning Electron Microscopy, Scanning Electron Microscope and X-ray Diffraction were used to study and evaluate the integrity and reliability of the coating produced. The results have indicated the sustainability and suitability of the method adopted in the study with regards to the production of good and quality functionally graded thermal barrier coating with no spallation problem and having good adherence to the substrate. Graphical abstract: Highlights: Slurry based system was used to fabricate effective functionally graded thermal barrier coating for high temperature. Increase in the percentage of Yttria Stabilized Zirconia gives good thermal resistance of the coating. Appropriate percentage of Nickel powder in the composition reduced spallation of the coating. Bonding strength of the coating with substrate increases with an increase in the sintering cycles and number of layers.